DIS3L2-mediated RNA surveillance and extracellular vesicle packaging prevent innate immune activation by aberrant cellular RNAs - Sandra G. Williams; Soyeong Sim; Wilfried M. Guiblet; Jubin George; Jennifer C. Jones; Sandra L. Wolin (Proceedings of the National Academy of Sciences, 2025)
Although most studies of the RNAs within extracellular vesicles (EVs) have focused on messenger RNA (mRNA) and microRNAs (miRNAs), recent analyses have revealed that transfer RNAs (tRNAs) and other noncoding RNAs (ncRNAs) are far more abundant. However, the extent to which EV ncRNAs resemble overall cellular RNAs and the benefits to host cells of packaging them into EVs remain unknown. Here, we purified EVs from the culture media of mouse and human cells and characterized their RNA components using high-throughput sequencing and Northern blotting. We report that EVs are enriched for numerous aberrant ncRNAs, including ncRNA fragments, ncRNAs that have failed to mature, and short structured introns. Many RNAs contain oligouridine tails, a modification that can promote degradation by DIS3L2, an exoribonuclease that degrades defective structured ncRNAs. Both the numbers of EVs released and the fractions of tailed RNAs in EVs increase on DIS3L2 depletion, indicating that EV packaging of aberrant ncRNAs occurs in competition with DIS3L2 decay. Multiple type I interferon-stimulated genes (ISGs) are upregulated on DIS3L2 depletion, and cells treated with a neutral sphingomyelinase inhibitor that reduces exosome biogenesis show moderate ISG upregulation, an effect that is enhanced in DIS3L2-depleted cells and accompanied by accumulation of aberrant ncRNAs in cellular RNA. Thus, DIS3L2 degradation and packaging of aberrant RNAs into vesicles may prevent these RNAs from activating innate immune sensors and triggering an interferon response.